PENGUATAN LITERASI GIZI MELALUI PROGRAM GEMARI (GERAKAN MENCEGAH ANEMIA REMAJA PUTRI): PELATIHAN KREASI KUDAPAN BERBASIS IKAN UNTUK REMAJA PUTRI SEBAGAI UPAYA PENCEGAHAN DAN PENURUNAN ANGKA KEJADIAN ANEMIA GIZI BESI - Diesna Sari; Fauziah Fauziah; Anisa Dwirizky Abdullah (Universitas Mataram, 2026)
Iron deficiency anemia remains a common health problem experienced by adolescent girls and can impact learning concentration and productivity. Efforts to improve nutritional literacy are one of the important strategies in preventing anemia in adolescents. This community service activity aims to enhance the knowledge and skills of adolescent girls in anemia prevention through the GEMARI Program (Gerakan Mencegah Anemia Remaja Putri/Movement to Prevent Anemia in Adolescent Girls), which was developed from previous research findings. The activity was carried out at SMP Negeri 1 Campalagian, targeting 24 adolescent girls. The activity methods included nutrition education on anemia prevention, an interactive question-and-answer session, and training on making fish-based snacks as a source of animal protein and iron. Furthermore, training on the use of health measurement tools (hemoglobin meters, scales, and height measuring devices) was also provided to the school health unit (UKS) teachers.Knowledge evaluation was conducted using pretest and posttest. The results showed an increase in participants' knowledge after the education, where the